2020
DOI: 10.1108/jfp-02-2020-0007
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective case note review of young people in transition from adolescent medium secure units to adult services

Abstract: Purpose There is substantial evidence that young people moving from child and adolescent mental health services to adult services are more likely to experience poor transitions. However, little is known about the care pathways of young people transitioning from forensic services. This retrospective case note review sought to examine the clinical characteristics, transition pathways and psychosocial indicators of transition outcomes amongst young people in forensic medium secure services discharged to adult ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Most included studies used data extraction and coding tools specifically designed for the purpose of the study. Eight studies reported assessing their tool for reliability or using a tool with proven psychometric properties; however, none reported any psychometric values (Appleton, 2021; Asl, 2014; Livanou, Lane, D'Souza, & Singh, 2020; McNicholas et al., 2015; McNicholas & Singh, 2015; Reale, Costantino, Sequi, & Bonati, 2018; Singh, 2012, 2013, 2014, 2015; Singh et al., 2010, 2021; Tatlow‐Golden et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most included studies used data extraction and coding tools specifically designed for the purpose of the study. Eight studies reported assessing their tool for reliability or using a tool with proven psychometric properties; however, none reported any psychometric values (Appleton, 2021; Asl, 2014; Livanou, Lane, D'Souza, & Singh, 2020; McNicholas et al., 2015; McNicholas & Singh, 2015; Reale, Costantino, Sequi, & Bonati, 2018; Singh, 2012, 2013, 2014, 2015; Singh et al., 2010, 2021; Tatlow‐Golden et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 24 papers describing 19 unique studies that focused on the transition of young people to AMHS regardless of their specific mental health condition (see Table ). Twelve studies included participants with any MH diagnoses without further specification (Adamopoulos & Samuel, 2021; Cohen, Klodnick, Kramer, Strakowski, & Baker, 2020; Garcia, Boix, Vegue, & De Angel, 2019; Islam et al., 2016; Leeb et al., 2020; Livanou et al., 2020; McNicholas et al., 2015; Paul et al., 2013; Pottick, Bilder, Vander Stoep, Warner, & Alvarez, 2008; Reneses et al., 2018; Saour, 2021; Singh et al., 2010, 2021; Stagi, Galeotti, Mimmi, Starace, & Castagnini, 2015). One study focused on ‘serious’ mental health disorders and provided the following example: schizophrenia spectrum, bipolar and major depressive disorders (Cohen et al., 2020).…”
Section: Transition From Child To Amhs For Young People With Varied M...mentioning
confidence: 99%
See 2 more Smart Citations
“…All local collaborators (five consultant forensic psychiatrists and one consultant forensic psychologist) completed a mapping exercise a priori regarding the number of young people eligible to transition within the next 6–9 months. The mapping tool was distributed to local collaborators between May 30th, 2016 and November 30th, 2016 and collected information about annual transition caseloads, demographics of the cohort and standard transition preparation procedures ( Livanou et al, 2020 ). The same mapping exercise was used in the TRACK study which is the largest UK study exploring transition outcomes from mainstream CAMHS to adult-oriented settings ( Singh et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%